Decoupling : gender injustice in China's divorce courts - Michelson, Ethan (Cambridge studies in law and society., 2022)
Michelson's analysis of almost 150,000 divorce trials reveals routine and egregious violations of China's own laws upholding the freedom of divorce, gender equality, and the protection of women's physical security. Using 'big data' computational techniques to scrutinize cases covering 2009-2016 from all 252 basic-level courts in two Chinese provinces, Henan and Zhejiang, Michelson reveals that women have borne the brunt of a dramatic intensification since the mid-2000s of a decades-long practice of denying divorce requests. This book takes the reader upstream to the institutional sources of China's clampdown on divorce and downstream to its devastating and highly gendered human toll, showing how judges in an overburdened court system clear their oppressive dockets at the expense of women's lawful rights and interests. This book is a must-read for anyone interested in Chinese courts, judicial decision-making, family law, gender violence, and the limits and possibilities of the globalization of law.This title is also available as Open Access on Cambridge Core.